Increased circulating CC chemokine levels in the metabolic syndrome are reduced by low‐dose atorvastatin treatment: evidence from a randomized controlled trial. (27th April 2013) - Loughrey, Brona V.; McGinty, Ann; Young, Ian S.; McCance, David R.; Powell, Lesley A.
Summary: Objective: Central obesity and insulin resistance are key components of the metabolic syndrome, which is associated with an increased risk of cardiovascular disease. In obesity, CC chemokines, such as monocyte chemotactic protein‐1 (MCP‐1), macrophage inhibitory protein‐1β (MIP‐1β) and eotaxin‐1 and their respective receptors, are critically involved in peripheral monocyte activation and adipose tissue infiltration. The aim of the current study was to examine whether low‐dose atorvastatin (10 mg/d) treatment modulated serum levels of CC chemokines in metabolic syndrome subjects. Materials and Methods: Serum levels of MCP‐1, eotaxin‐1, MIP‐1β, C reactive protein (CRP) and interleukin‐6 (IL‐6) were measured in lean control and metabolic syndrome subjects at baseline, and following a 6‐week randomized placebo‐controlled clinical trial of atorvastatin (10 mg/d). Peripheral CD14 + monocytes were isolated and mRNA levels of MCP‐1, MIP‐1 β and CCR5 determined. Results: Serum MCP‐1 ( P  = 0·02), eotaxin‐1 ( P  = 0·02) and MIP‐1β ( P  = 0·03), CRP ( P  < 0·001) and IL‐6 ( P  = 0·006) were significantly increased in metabolic syndrome in comparison with lean controls. Furthermore, CD14 + peripheral monocyte mRNA expression of the chemokine receptor, CCR5, of which MIP‐1β and eotaxin‐1 are ligands, was increased two‐fold in the metabolic syndrome group ( P  = 0·03). In addition to the expected improvements in lipid profile, atorvastatin treatment significantly reduced circulating eotaxin‐1 ( P  < 0·05), MIP‐1β ( P  < 0·05) levels and CD14 + peripheral monocyte CCR5 mRNA expression ( P  = 0·02). Conclusion: These results support a model whereby atorvastatin treatment, by inhibiting CD14 + monocyte CCR5 expression, may inhibit monocyte trafficking, reduce chronic inflammation and, thus, lower circulating levels of CC chemokines.